Cardioprotection Reloaded: Reflections on 40 Years of Research - Pasquale Pagliaro; Giuseppe Alloatti; Claudia Penna (Antioxidants)
Over the past four decades, cardioprotective research has revealed an extraordinary complexity of cellular and molecular mechanisms capable of mitigating ischemia/reperfusion injury (IRI). Among these, ischemic conditioning has emerged as one of the most influential discoveries: brief episodes of ischemia followed by reperfusion activate protective programs that reduce myocardial damage. These effects can be elicited locally (pre- or postconditioning) or remotely (remote conditioning), acting mainly through paracrine signaling and mitochondria-linked kinase pathways, with both early and delayed windows of protection. We have contributed to clarifying the roles of mitochondria, oxidative stress, prosurvival kinases, connexins, extracellular vesicles, and sterile inflammation, particularly via activation of the NLRP3 inflammasome. Despite robust preclinical evidence, clinical translation of these approaches has remained disappointing. The challenges largely stem from experimental models that poorly reflect real-world clinical settings—such as advanced age, comorbidities, and multidrug therapy—as well as the reliance on surrogate endpoints that do not reliably predict clinical outcomes. Nevertheless, interest in multi-target protective strategies remains strong. New lines of investigation are focusing on emerging mediators—such as gasotransmitters, extracellular vesicles, and endogenous peptides—as well as targeted modulation of inflammatory responses. Future perspectives point toward personalized cardioprotection tailored to patient metabolic and immune profiles, with special attention to high-risk populations in whom IRI continues to represent a major clinical challenge.